Self-Care Behavior in Diabetes Mellitus Patients Using Herbals as a Complement to Treatment - Anita Joeliantina; Hepta Nur Anugrahini (Health Notions, 2020)
Diabetes mellitus (DM) is a chronic disease that requires treatment or management in the long term. DM patients have a tendency to seek other treatment besides medical treatment. The use of herbs is one of the choices for DM patients in complementing self-care, especially in the treatment component. This study aims to explore in depth about self-care behavior in DM patients who use herbs as a complement to medical treatment. This study used a qualitative design with a phenomenological method approach. Participants were determined by purposive sampling technique as many as 9 participants. Data collection was carried out in August and October 2015 with in-depth interview techniques. Data analysis using Interpretative Phenomenological Analysis. The data validation was done by using triangulation technique. There are three themes generated in this study, namely: 1) reasons for going to health services, 2) patient expectations after being diagnosed with diabetes, and 3) diabetes self-care. DM patients who have a tendency to use herbs as a complement to medical treatment must continue to carry out self-care regularly so that their blood sugar levels are controlled. The pattern of diabetes self-care behavior needs the attention of health workers, so that DM patients continue to carry out self-care regularly when using herbs as a companion to medical treatment. Keywords: diabetes mellitus; herbs; self-care